Sinergi Negatif Burnout dan Adiksi Smartphone terhadap Capaian Akademik Mahasiswa Kesehatan - Antonius Ngadiran; Srihesty Manan; Berlyna Dameyanti Saragih (Universitas Faletehan, 2026)
High academic pressure in health sciences colleges poses a risk of causing emotional exhaustion or burnout and encouraging maladaptive behaviors such as smartphone addiction. Both factors are often considered as major obstacles to students' academic achievement. This study was conducted to analyze the simultaneous influence of burnout and smartphone addiction on students' academic performance. This is a quantitative study with a cross-sectional design, involving 300 health sciences students as respondents who were selected using the purposive sampling technique and the Slovin formula with a margin of error of about 5% (0.05). Data analysis was performed using path analysis to test the influence between variables. Research findings indicated that burnout has a significant negative effect on academic achievement (b = -0.264; p = 0.000), suggesting that higher levels of academic exhaustion lead to lower student GPA. Conversely, smartphone addiction was not found to have a significant direct influence on academic achievement (p = 0.514). This study concluded that burnout is the primary predictor that negatively impacts the academic outcomes of health sciences students. Therefore, educational institutions need to prioritize stress management programs and burnout prevention interventions to maintain the stability of students' academic performance.